2019
DOI: 10.1001/jamanetworkopen.2019.16439
|View full text |Cite
|
Sign up to set email alerts
|

Association of Longitudinal β-Amyloid Accumulation Determined by Positron Emission Tomography With Clinical and Cognitive Decline in Adults With Probable Lewy Body Dementia

Abstract: Key PointsQuestionWhat is the trajectory of β-amyloid accumulation over time, and how is it associated with clinical and cognitive decline among patients with probable dementia with Lewy bodies?FindingsThis cohort study of 175 participants found that the cumulative density of β-amyloid accumulation by time in years followed a sigmoid-shaped form among patients with probable dementia with Lewy bodies as well as among cognitively unimpaired participants who were matched by age, sex, and apolipoprotein e4 status.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 48 publications
1
22
0
2
Order By: Relevance
“…Indeed, the identification of consistent disease progression markers is still an open challenge for DLB. Recently, a growing number of studies identified EEG, imaging or CSF abnormalities to be associated with faster progression already in early DLB stages [2224]. However, these techniques definitively need further validations to be applied in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the identification of consistent disease progression markers is still an open challenge for DLB. Recently, a growing number of studies identified EEG, imaging or CSF abnormalities to be associated with faster progression already in early DLB stages [2224]. However, these techniques definitively need further validations to be applied in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…A weak correlation between cortical amyloid burden and cognitive decline emerged [ 24 ], likely because currently available amyloid-PET tracers bind fibrillary insoluble amyloid plaques and not the more toxic amyloid oligomers [ 25 ]. Additionally worth noting is that amyloid-PET positivity may also be present in neurodegenerative dementia other than AD, including FTLD and dementia with Lewy bodies (DLB) [ 26 , 27 ]. For all these reasons, using amyloid-PET imaging for screening candidates in clinical trials has been criticized, while the employment of multiple, more specific neurodegeneration biomarkers should be encouraged [ 1 ].…”
Section: The Role Of Pet Imaging In Neurodegenerative Conditionsmentioning
confidence: 99%
“…Few investigations have assessed the longitudinal pathological AD-related changes in DLB patients. Nedelska et al [ 213 ] determined the trajectory of β-amyloid accumulation in a cohort of 35 consecutive patients with DLB from the Mayo Clinic Alzheimer Disease Research Center. They also investigated the associations of β-amyloid accumulation with measures of clinical and cognitive decline over time in DLB.…”
Section: Imaging Biomarkers Of Dlbmentioning
confidence: 99%
“…Higher baseline PiB and change in PiB were associated with a more rapid clinical and cognitive decline over time. Measuring the change in PiB may have implications for designing anti–β-amyloid randomized clinical trials for DLB patients [ 213 ]. Sarro et al [ 207 ] investigated the associations between baseline PIB binding and the longitudinal rates of grey matter atrophy in a cohort of clinically diagnosed patients with dementia with Lewy bodies, who were consecutively recruited to the Mayo Clinic Alzheimer’s Disease Research Centre.…”
Section: Imaging Biomarkers Of Dlbmentioning
confidence: 99%